SISTEM HIDROPONIK WICK MENGGUNAKAN AIR CUCIAN BERAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Rikardus Tinja; I Ketut Sumantra; I Ketut Widnyana; Ni Putu Pandawani; I Gusti Ngurah Alit Wiswasta (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2023)
So far, hydroponic cultivation uses chemical fertilizers that have been formulated and are ready to be used by farmers, but not much use of organic fertilizers. In this study using a nutrient source from rice washing water with the aim of this research is to analyze the effect of rice washing water concentration on the growth and yield of land kangkung plants. Determining the best concentration of rice washing water in hydroponic cultivation of land spinach. This study used a randomized block design (RAK) with enem, namely treatment (A0) without washing rice (water pump), (A1) treatment with rice washed water 10 ml/1 liter of water, (A2) treatment with rice washing water 20 ml /1 liter of water, (A3) treatment of rice washing water 30 ml/1 liter of water, (A4) treatment of rice washing water 40 ml/1 liter of water, (A5) treatment of rice washing water 50 ml/1 liter of water, each treatment repeated four times so that the number of all treatments became 24. The results showed 50 ml/1liter of water gave the best growth results for all observed parameters, namely: plant height (cm), number of leaves (strands), leaf area (cm), leaf color, total fresh weight of plants (g), and total oven-dry weight of plants (g).